Sudan Country Economic Memorandum : Realizing the Potential for Diversified Development - World Bank Group (World Bank, Washington, DC, 2016)
From 1999 to 2011 Sudan had a period where it benefited from extensive discoveries of natural wealth through oil. But the oil economy had also clear symptoms of Dutch disease. Agriculture suffered from neglect, and there were urgent calls to invest natural resource rents into economic diversification efforts. Relief to Sudan’s external debt crisis will be critical. The country economic memorandum (CEM) starts out with a series of simulations and a review of recent key literature on growth and diversification with the aim of defining a suitable approach for growth and diversification for Sudan. The sectoral structure of Sudan’s economy shows the growing importance of agriculture, less importance of extractives, and relative stability of other sectors (manufacturing, services) by 2030. Looking at other economies that were successful in their diversification efforts shows that they were able to broaden their endowments base by maximizing a triad of institutions to deliver services that ultimately increase productivity. The CEM finds that there is a case for Sudan to approach growth through diversification from two angles: the production and the endowment base, both of which rely on the effective utilization of key institutions. This analysis therefore uses a sectoral focus and looks at agriculture as sources for diversification, but also makes the case that trading of goods and services - especially of the higher value-added kind - can be a means to grow the endowment base of the country.